Biosynthetic pathway of indole-3-acetic acid in ectomycorrhizal fungi collected from northern Thailand - Jaturong Kumla (2020)
© 2020 Kumla et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Indole-3-acetic acid (IAA) is an imperative phytohormone for plant growth and development. Ectomycorrhizal fungi (ECM) are able to produce IAA. However, only a few studies on IAA biosynthesis pathways in ECM fungi have been reported. This study aimed to investigate the IAA biosynthesis pathway of six ECM cultures including Astraeus odoratus, Gyrodon suthepensis, Phlebopus portentosus, Pisolithus albus, Pisolithus orientalis and Scleroderma suthepense. The results showed that all ECM fungi produced IAA in liquid medium that had been supplemented with L-tryptophan. Notably, fungal IAA levels vary for different fungal species. The detection of indole-3-lactic acid and indole-3-ethanol in the crude culture extracts of all ECM fungi indicated an enzymatic reduction of indole-3-pyruvic acid and indole-3-acetaldehyde, respectively in the IAA biosynthesis via the indole-3-pyruvic acid pathway. Moreover, the tryptophan aminotransferase activity confirmed that all ECM fungi synthesize IAA through the indole-3-pyruvic acid pathway. Additionally, the elongation of rice and oat coleoptiles was stimulated by crude culture extract. This is the first report of the biosynthesis pathway of IAA in the tested ECM fungi.